Gündem Newspaper =Gündem Gazetesi - N/A (Eastern Mediterranean University Faculty of Communication =Doğu Akdeniz Üniversitesi İletişim Fakültesi, 2010)
[Abstract Not Available]
This issue of Gündem Newspaper includes both English and Turkish sections. (Gündem Gazetesi'nin bu sayısı İngilizce ve Türkçe kısımlar içermektedir.)
Keywords: EMU Faculty of Communication - Faculty Newspaper - Student Newspaper - University News; DAÜ İletişim Fakültesi - Fakülte Gazetesi - Öğrenci Gazetesi - Üniversite Haberleri